2006
DOI: 10.1593/neo.05652
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Polyphenon E, Red Ginseng, and Rapamycin on Benzo(a)pyrene-Induced Lung Tumorigenesis in A/J Mice

Abstract: The objective of this investigation was to determine the efficacy of several novel agents in preventing lung tumorigenesis in mice. We evaluated polyphenon E, red ginseng, and rapamycin in A/J mice treated with the tobacco-specific carcinogen benzo(a)pyrene for their ability to inhibit pulmonary adenoma formation and growth. We found that treatment with polyphenon E exhibited a significant reduction on both tumor multiplicity and tumor load (tumor multiplicity x tumor volume) in a dose-dependent fashion. Polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…In addition to preventing tumorigenesis, our data show that administration of rapamycin to established NNK-induced tumors decreases tumor size but does not affect tumor multiplicity. This is consistent with a study by Yan et al who showed that treatment with a higher dose of rapamycin (2.0 mg/kg) on a daily (5 of 7 days) schedule for 14 weeks, beginning 12 weeks after administration of a polycyclic aromatic hydrocarbon [benzo(a)pyrene], reduced lung tumor load by 84% (21). Similar to our results, Yan et al did not observe a reduction in tumor multiplicity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to preventing tumorigenesis, our data show that administration of rapamycin to established NNK-induced tumors decreases tumor size but does not affect tumor multiplicity. This is consistent with a study by Yan et al who showed that treatment with a higher dose of rapamycin (2.0 mg/kg) on a daily (5 of 7 days) schedule for 14 weeks, beginning 12 weeks after administration of a polycyclic aromatic hydrocarbon [benzo(a)pyrene], reduced lung tumor load by 84% (21). Similar to our results, Yan et al did not observe a reduction in tumor multiplicity.…”
Section: Discussionsupporting
confidence: 93%
“…Combined with the results obtained by Wislez et al (20) and Yan et al (21), our data provide a strong rationale to consider testing rapamycin in smokers who are at high risk to develop lung cancer. What are the issues that limit the application of these findings to a clinical trial?…”
Section: Discussionsupporting
confidence: 78%
“…This preparation has been investigated extensively in terms of toxicology and pharmacokinetics, and is in phase I and phase II clinical chemoprevention trials at different institutions (25)(26)(27)(28). In the present study, the effects of Polyphenon E and caffeine on the progression of NNKinduced lung adenoma to adenocarcinoma in A/J mice were examined.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that 0.5% PPE in drinking fluid, given during weeks 20 to 52 after NNK treatment, significantly inhibits lung tumor progression from adenoma to adenocarcinoma (8). It has also been shown that PPE given at the postinitiation stage significantly lowers both tumor multiplicity and tumor load in a dose-dependent manner in a benzo(a)pyrene-induced lung tumor model (9). The National Cancer Institute has assisted the development of PPE as an agent for human chemoprevention studies.…”
mentioning
confidence: 85%